Anticardiolipin Antibodies in Children with Helicobacter pylori Infection. Issue 6 (9th April 2015) - Sarıcı, Serdar Umit; Gursel, Orhan; Kurekci, Emin; Kesik, Vural; Atay, Avni; Okutan, Vedat; Inal, Ali; Pekel, Aysel; Ozguven, Mehmet Ali; Ozcan, Okan
Abstract: Background: Anticardiolipin (aCL) antibodies are associated with thrombosis and have an important role in the etiology of diseases such as stroke and myocardial infarction whose etiologies were based on thrombosis. H. pylori has been proposed to be responsible for the pathophysiology of some diseases including stroke, myocardial infarction, thrombosis, and autoimmune diseases. From this point of view, we hypothesized a possible relationship between H. pylori infection and aCL antibodies and initially aimed to determine the prevalence of aCL antibody positivity in children with H. pylori infection. Materials and Methods: Anticardiolipin antibodies were studied in 84 patients before and after eradication therapy and in a control group including 40 children. Results: The pretreatment aCL IgA (median 12.78 APL/mL), aCL IgM (median 21.60 MPL/mL), and aCL IgG antibody levels (median 14.22 GPL/mL) were significantly higher than those of post‐treatment results (median 5.38 APL/mL, 7.02 MPL/mL, and 6.64 GPL/mL, respectively) and controls (median 5.90 APL/mL, 4.80 MPL/mL, and 4.81 GPL/mL, respectively). Anticardiolipin antibodies revealed no significant differences between the study group after therapy and the control group. Conclusions: In our particular experience, H. pylori can cause aCL antibody positivity in children and eradication of H. pylori provides the disappearance of these antibodies.